PENGARUH KUALITAS PRODUK DAN PROMOSI PRODUK TERHADAP KEPUTUSAN PEMBELIAN LEM KUNING FOX (STUDI KASUS PADA KONSUMEN PT. AICA INDRIA) - Hasti Pramesti Kusnara; Mariati Tirta Wiyata (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of this writing is to find out how much influence the product quality and promotion of products on consumer purchasing decisions PT. Aica Indria. The research conducted was by distributing questionnaires using the Slovin formula. From the results of multiple linear regression analysis, the results of the equation Y = 16.435 + 0.359X1 + 0.282X2 and the correlation coefficient, which is equal to 0.224 for Product quality (X1) and 0.287 for Product Promotion (X2), which means the percentage contribution of the Product quality effect is 22.4% while the rest 77.6% is influenced by other variables. If joint testing is carried out between the Product quality and Product Promotion variables, then the correlation value of determination is 0.287, which means the effect of Product quality and Product Promotion has a percentage of 28.7% and the remaining 71.3% is influenced by other variables. Based on the results of the hypothesis test obtained t count for product quality of 4,328, t count for product promotion amounted to 2,290, with t table of 1,660 obtained from t distribution table for df = 100-2 and level of significant 0.05. In other words, Ha was accepted and Ho was rejected because tcount> ttable. Based on hypothesis testing for product product quality and promotion of purchasing decisions, the fcount value of 19,491 is obtained with a significant level of 0,000 where 0,000 <0.05 and also Fcount> Ftable or 19,491> 3.09, thus Ho is rejected and Ha is accepted. Based on the results of this study it can be concluded that there is a relationship between product product quality and promotion of purchasing decisions, if product product quality and promotion can be improve properly it can increase purchasing decisions.